2006
DOI: 10.1038/nm1392
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead protein FoxO1 mediates Agrp-dependent effects of leptin on food intake

Abstract: Leptin controls food intake by regulating the transcription of key neuropeptides in the hypothalamus. The mechanism by which leptin regulates gene expression is unclear, however. Here we show that delivery of adenovirus encoding a constitutively nuclear mutant FoxO1, a transcription factor known to control liver metabolism and pancreatic beta-cell function, to the hypothalamic arcuate nucleus of rodents results in a loss of the ability of leptin to curtail food intake and suppress expression of Agrp. Conversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
377
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(401 citation statements)
references
References 41 publications
20
377
2
2
Order By: Relevance
“…We have previously shown that SOCS3 expression is Cre-dependent, and its expression is upregulated approximately twofold in Cre-expressing cells upon recombination (6). The Tg.Agrp-Cre mice have been used and validated in a number of independent studies (7,(25)(26)(27)(28)(29)(30)(31). The resultant mutant mice, termed AgRP-SOCS3-OE, were born in Mendelian ratio with no detectable gross abnormalities.…”
Section: Expression Of Socs3 In Agrp Neurons Is Dynamically Modulated Inmentioning
confidence: 99%
“…We have previously shown that SOCS3 expression is Cre-dependent, and its expression is upregulated approximately twofold in Cre-expressing cells upon recombination (6). The Tg.Agrp-Cre mice have been used and validated in a number of independent studies (7,(25)(26)(27)(28)(29)(30)(31). The resultant mutant mice, termed AgRP-SOCS3-OE, were born in Mendelian ratio with no detectable gross abnormalities.…”
Section: Expression Of Socs3 In Agrp Neurons Is Dynamically Modulated Inmentioning
confidence: 99%
“…Among the targets of activated Akt are mTOR and the forkhead transcription factor FoxO1 (19). Recently, it was reported that FoxO1 in hypothalamus is involved in regulating neuropeptide expression and food intake (13,14). Pomc expression partially depends on the PDK-1-FoxO1 signaling pathway.…”
Section: Loss Of Pdk-1 In Pomc Neurons Blunts Influx Of Ca 2ϩ By Leptinmentioning
confidence: 99%
“…FoxO1 is a downstream element of insulin signaling: it is phosphorylated and inhibited in a PI(3)K -dependent manner (1). Recent FoxO1 studies using adenoviral delivery to the hypothalamus have demonstrated that FoxO1 increased food intake through the activation of AgRP and/or Npy gene expression and the inhibition of Pomc gene expression (13,14). Belgardt et al (4) delineated the importance of pathways downstream of PI(3)K in POMC neurons by using mice in which Pdk1 was inactivated specifically in POMC neurons.…”
mentioning
confidence: 99%
“…Previously, we have identified that forkhead boxcontaining protein 1 (FOXO1) may act at a step downstream of STAT3 phosphorylation to prevent activated STAT3 from interacting with the SP1-Pomc promoter complex, thereby repressing transcriptional activation [10]. FOXO1 may also inhibit phosphorylated STAT3 (pSTAT3) action directly at the promoter level [11,12].…”
Section: Introductionmentioning
confidence: 99%